Insight into Invasive Species (Mikania micrantha), Its Control Measures and Programmes in Nepal - Paudel, Rajan P (The Initiation, 2011)
Invasive species adversely affects the ecology and habitat of the species existing in a particular region. They are one of the top threats to the biodiversity of life on Earth. Mikania micrantha is spreading like a wildfire in Nepal whose effect on Rhino habitat is being studied in Chitwan National Park. Various mechanical, chemical and biological methods of control for Mikania are available. It's likely to be more cost effective to prevent the spread of invasive species in the first place than to tackle the biodiversity crisis once they have become established. DOI: http://dx.doi.org/10.3126/init.v4i0.5544 The Initiation Vol.4 2011 115-119